2022
DOI: 10.1177/11786302221127856
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Wastewater Irrigation on the Microbiological Quality of Vegetables in Northeast Ethiopia: Implication for Food-Borne Infection and Intoxications

Abstract: background: Cultivation of vegetables using untreated wastewater is a common phenomenon in many drought-prone areas of the world. Consumption of such microbiologically unsafe vegetable increase the risk of food-borne diseases. As a result, evaluating the effect of wastewater irrigation on the microbiological quality of vegetables would be beneficial to consumers’ health. method: A total of 192 vegetable samples (lettuce, cabbage, carrot, and tomato) and 64 irrigation water samples were collected and analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…These findings demonstrated the synergetic action between the combined fungal species in using organic pollutants as a sole source of carbon or else degrading organic compounds in the presence of growth nutrients from cheap sources. Data from this study supports that the tested fungal strains were highlighted in several studies by their removal efficiency and potential for decomposing xenobiotic organic compounds from wastewater [25,27,30]. In some references, wood-decaying fungi are described as factories of lignin-modifying enzyme production, which is involved in fungal bioremediation processes, including laccases, manganese peroxidases, and lignin peroxidases [31,32].…”
Section: Screening Of Single and Consortia Fungal Culture For Cod Rem...supporting
confidence: 78%
“…These findings demonstrated the synergetic action between the combined fungal species in using organic pollutants as a sole source of carbon or else degrading organic compounds in the presence of growth nutrients from cheap sources. Data from this study supports that the tested fungal strains were highlighted in several studies by their removal efficiency and potential for decomposing xenobiotic organic compounds from wastewater [25,27,30]. In some references, wood-decaying fungi are described as factories of lignin-modifying enzyme production, which is involved in fungal bioremediation processes, including laccases, manganese peroxidases, and lignin peroxidases [31,32].…”
Section: Screening Of Single and Consortia Fungal Culture For Cod Rem...supporting
confidence: 78%
“…Specifically, it increased from 8.3% to 35% in tomatoes, 1.7% to 46.2% in cabbage, and 1.5% to 20% in carrots. Previous research 26 indicated a positive correlation between the total number of fecal coliform bacteria present in vegetables and their number in irrigation water contaminated with wastewater. This study also reported that some vegetables, such as carrots, are less polluted than others, whereas cabbage recorded the highest levels of contamination.…”
Section: Resultsmentioning
confidence: 93%